Cell salvage in bacterially contaminated surgical fields – A scoping review - Joeri Slob; Pim Hondebrink; Ankie W.M.M. Koopman – van Gemert; Margriet E. van Baar; Cornelis H. van der Vlies; Seppe S. H. A. Koopman (PLoS ONE, 2026)
Objective This scoping review systematically examines the use of intraoperative cell salvage in bacterially contaminated surgical settings, examining contamination levels, decontamination strategies, and clinical outcomes following the reinfusion of contaminated salvaged blood. Methods Following the Joanna Briggs Institute methodology and the PRISMA extension for scoping reviews, comprehensive searches were conducted in MEDLINE, Embase, Web of Science, and Cochrane CENTRAL. Eligible studies included primary empirical research reporting bacterial contamination of salvaged blood confirmed by culture, as well as studies reporting on decontamination strategies or clinical outcomes following reinfusion, across any surgical setting. Data was extracted and synthesized descriptively. Key findings were summarized in structured tables. Results Thirty-nine studies, involving 1654 patient, met the inclusion criteria. Bacterial contamination was consistently reported, with positive culture rates varying widely. Methodological quality was assessed for all studies, except the ex-vivo studies. Decontamination strategies, including leukocyte depletion filtration (10 studies) and antibiotic additives (4 studies), reduced contamination, though effectiveness varied. Among 26 studies, involving 1203 patients, who received reinfused salvaged blood, postoperative infections were reported in 15 studies. A total of 55 cases of postoperative bacteraemia were identified. Only five studies described a plausible microbiological link between the reinfused blood and subsequent infection, involving nine patients in whom the isolated pathogen matched the organism cultured from the salvaged blood. Conclusion Bacterial contamination of salvaged blood occurred frequently, even in procedures not typically classified as contaminated. Decontamination strategies demonstrated variable effectiveness in reducing bacterial contamination. Despite contamination, a potential microbiological link between reinfused salvaged blood and infection was described in only nine patients across five studies. However, substantial heterogeneity in methodologies and a small sample size of most studies makes it difficult to draw definite conclusions about safety. Therefore, we would advise to use cell salvage in known bacterial contaminated areas on a case by case basis, after careful evaluation of the pros and cons, until future research defined safe contamination thresholds, evaluated the effectiveness of decontamination techniques, and assessed clinical outcomes in standardized and controlled settings.